Neurological aspects of menopause – influence of initiating hormonal replacement therapy. III Cerebrovascular disorders - M. Kanadys, Wiesław (Menopause Review/Przegląd Menopauzalny, 2003)
Cerebrovascular diseases are third cause of death, main cause of disability, frequent cause of depression, as well leading cause of dementia. There is a apparent discrepancy between neuroprotective effects of estrogen proved on both neuronal culture and animal models and results of clinical studies of hormone replacement therapy (HRT) for the primary or secondary prevention of stroke. Datas on influence of current use of hormonotherapy on incidence of nonfatal stroke in total and ischemic stroke are conflicting, but with a majority of studies showing a tendency to an increased risk. Paradoxically, the majority of studies show reduction of risk of fatal stroke, as well as distinct beneficial effect on incidence of hemorrhagic stroke. No benefit was observed in stroke severity in women receiving HRT. The Women’s Estrogen for Stroke Trial (WEST) reported disappointing results for use HRT in women with previous stroke or transient ischemic attack: estrogens do not reduce mortality or risk of recurrence of stroke. This therapy should not be prescribed for the secondary prevention of cerebrovascular disease. Currently there are no sufficient clinical evidence proving that hormonotherapy has protective effect on central nervous system.